Country Partnership Framework for the Kingdom of Bhutan for the Period FY2021-24 - World Bank Group (World Bank, Washington, DC, 2021)
The country’s unique philosophy is expressed by Bhutan’s Gross National Happiness (GNH) as the guiding principle of development. Bhutan is at a crossroads: It can maintain the current pattern of development—with rising inequality—or develop a vibrant private sector to generate jobs and diversify the economy, building resilience to future external shocks. The overarching priority of this Country Partnership Framework (CPF) is job creation. This CPF presents an integrated framework of WBG support to help Bhutan achieve inclusive and sustainable development through private sector–led job creation.